A stain-resistant tunnel wall finish coating and a method for preparing the same
Patent Information
- Application Number
- CN202611239347.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-17
AI Technical Summary
[0005]本发明的目的在于针对现有疏水型饰面涂料虽然具有较高水接触角,但柴油油烟仍会进入微纳结构并黏结炭黑颗粒的问题,提供一种耐沾污隧道壁面饰涂料及其制备方法
[0050]与现有技术相比,本发明提供了一种耐沾污隧道壁面饰涂料及其制备方法,具备以下有益效果:并非仅依靠提高水接触角,而是通过空气侧拒油释污、基体侧化学锚定和片层边缘通道封闭三种作用共同抑制柴油油烟污染。
Smart Images

Figure CN122772478B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of functional coatings for buildings and protective materials for transportation infrastructure, specifically to a stain-resistant tunnel wall coating and its preparation method that can inhibit the penetration of oily components in diesel fumes into the coating, reduce the adhesion of carbon black particles, and facilitate water washing and cleaning. Background Technology
[0002] In highway tunnels, urban underpasses, underground parking garages, and other enclosed or semi-enclosed spaces with high vehicular traffic, wall finishes are subjected to the combined effects of vehicle exhaust, diesel fumes, tire wear particles, road dust, and condensation. Unlike the water-based mud and dust that comes into contact with ordinary building exteriors, diesel fumes typically contain carbon black particles, incompletely burned hydrocarbons, lubricating oil volatiles, and other low-surface-tension organic components.
[0003] Existing stain-resistant coatings typically employ fluorinated resins, silicone resins, hydrophobically modified nano-silica, or micro / nano rough structures to increase the water contact angle. While these coatings offer some repellency against waterborne contaminants, a high water contact angle does not equate to resistance to diesel fumes. Liquid or semi-liquid hydrocarbons in diesel fumes can wet ordinary hydrophobic surfaces and penetrate the coating along the pores between micro / nano particles, the edges of lamellar plates, and the resin-filler interface, carrying carbon black particles into the surface structure during this penetration. As the oily components oxidize, thicken, or partially cure, the carbon black particles become fixed within the coating, making it difficult to restore the original color even with high-pressure water washing or neutral cleaning agents, ultimately resulting in irreversible blackening.
[0004] Simply increasing the surface fluorine content may also have the following drawbacks: all surfaces of symmetrical hydrophobic particles have low surface energy, resulting in insufficient compatibility and chemical bonding between the particles and the water-based resin matrix, making them prone to detachment after long-term washing; excessive construction of micro-nano rough structures may increase the capillary channels and mechanical embedding sites that oil fumes can enter; although ordinary silica sol can improve the hardness of the coating film, it is difficult to form a continuous closed network that is stably bonded to the resin matrix at the edges of the sheet-like particles. Summary of the Invention
[0005] The purpose of this invention is to address the problem that although existing hydrophobic decorative coatings have a high water contact angle, diesel fumes can still enter the micro-nano structure and adhere to carbon black particles. This invention provides a stain-resistant tunnel wall decorative coating and its preparation method.
[0006] This invention achieves the following simultaneously through the synergistic effect of double-sided Janus sheet-like anti-smoke particles and capillary channel-sealing sol: 1. Reduce the adhesion of organic fumes to the air-side surface of the coating; 2. During the washing process, a hydration interface is formed through polyoxyethylene segments, promoting the removal of pollutants; 3. The matrix side of the flake particles is chemically anchored to the isocyanate crosslinking network through amino and / or hydroxyl groups; 4. The capillary channels of the sol containing epoxy silane hydrolysate and nano silica are closed, forming a silicon-oxygen network at the edge of the flake particles and the resin-filler interface, reducing the channels for the penetration of oily contaminants.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a stain-resistant tunnel wall coating, comprising component A and component B.
[0008] By weight, component A comprises: 35-55 parts of waterborne hydroxy acrylic dispersion; 10-25 parts of waterborne siloxane-modified polyurethane dispersion; 4-12 parts of double-sided Janus flake anti-smoke particles; 2-8 parts of capillary channel blocking sol; 10-25 parts of titanium dioxide; 5-20 parts of inorganic filler; 0.2-1.5 parts of dispersant; 0.1-0.8 parts of defoamer; 0.1-1.0 parts of rheology modifier; and 5-20 parts of water.
[0009] Component B includes 3 to 10 parts of water-dispersible aliphatic polyisocyanate.
[0010] The double-sided Janus sheet-like anti-smoke particles comprise a sheet-like inorganic matrix. The sheet-like inorganic matrix has a first main surface and a second main surface disposed opposite to each other.
[0011] The first main surface is grafted with fluorinated polyether segments and polyoxyethylene segments. The fluorinated polyether segments are used to reduce the adhesion of hydrocarbons in diesel fumes; the polyoxyethylene segments, in a dry state, together with the fluorinated polyether segments, form a low-pollution adhesion interface, which can be rearranged into the aqueous phase and form a hydration layer after contact with cleaning water, thereby promoting the removal of oil fume pollutants.
[0012] The second primary surface is grafted with amino and / or hydroxyl groups that can react with isocyanates. During the curing process of the finishing coating, the amino and / or hydroxyl groups on the second primary surface react with water-dispersible aliphatic polyisocyanates, anchoring the double-sided Janus flake-like anti-smoke particles into the cross-linked resin matrix.
[0013] The capillary channel blocking sol is composed of 3-glycidyl etheroxypropyltrimethoxysilane hydrolysate and nano-silica with a particle size of 8–30 nm. The mass ratio of the two on a dry matter basis is 1:1–4, and the solid content of the capillary channel blocking sol is 15–35 wt%.
[0014] During the coating curing process, the silanol groups in the capillary channel-sealing sol undergo condensation at the edges of adjacent sheet-like particles, the interface between the sheet-like particles and the resin, and the surface of the inorganic filler, forming a silicon-oxygen network containing Si-O-Si bonds; the epoxy groups in 3-glycidyl etheroxypropyltrimethoxysilane can also react with the amino groups on the second main surface of the double-sided Janus sheet-like anti-smoke particles, thereby improving the bonding stability between the sheet edge sealing network and the particles.
[0015] The sheet-like inorganic matrix is selected from one or more of synthetic fluorophlogopite, glass flakes, sheet-like alumina, and sheet-like boron nitride.
[0016] The median particle size of the sheet-like inorganic matrix is 6–25 μm, the thickness is 0.15–0.80 μm, and the aspect ratio is 30–120.
[0017] Preferably, the first main surface is formed by grafting fluorinated polyether silane and polyether silane together, and the mass ratio of fluorinated polyether silane to polyether silane is 3 to 9:1.
[0018] The number average molecular weight of the fluorinated polyether segments is 500 to 3000.
[0019] The molar content of ethylene oxide units in the polyoxyethylene segment is 60-100%.
[0020] The second main surface is formed by grafting aminosilane and / or hydroxysilane. The aminosilane is selected from one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0021] The hydroxysilane is a hydroxysilane hydrolysate obtained by acid hydrolysis of 3-glycidyl etheroxypropyltrimethoxysilane and partial ring opening of the epoxy group.
[0022] The double-sided Janus sheet-like anti-fouling particles are preferably prepared using an oil-water interface selective grafting method, including the following steps: J1. The sheet-like inorganic matrix is pre-wetted with water, and the pre-wetted sheet-like inorganic matrix is continuously added between the immiscible oil phase and the water phase, so that the sheet-like inorganic matrix spreads at the oil-water interface. J2. The oil phase contains fluorinated polyether silane and polyether silane, and the aqueous phase contains hydrolysates of amino silane and / or hydroxy silane. The reaction is carried out at 45-75°C for 0.5-3 hours, so that fluorinated polyether segments and polyoxyethylene segments are grafted onto the first main surface facing the oil phase, and amino and / or hydroxyl groups are grafted onto the second main surface facing the aqueous phase. J3. The reaction product is filtered, washed and dried to obtain double-sided Janus flake-shaped anti-smoke particles.
[0023] The oil phase is selected from one or more of isoalkanes, n-heptane, cyclohexane, and liquid paraffin. To reduce volatile organic compound emissions, low-aromatic isoalkanes with a boiling point of 160–220°C are preferred.
[0024] In industrial production, a horizontal oil-water interface reactor can be used. The reactor includes an oil phase layer, a water phase layer, an interface feed distributor, a low-shear propeller agitator, a continuous overflow port, and a solid-liquid separation device. A pre-wetted sheet-like inorganic matrix is added to the oil-water interface through a slit-type distributor at a rate of 5–50 kg / h, and the shear rate in the interface region is controlled at 10–80 s⁻¹. - ¹, to reduce the flipping and agglomeration of flaky particles.
[0025] After the reaction, the particles are subjected to sedimentation and phase separation, horizontal centrifugation or vacuum belt filtration, and then washed with alcohol and water in sequence, followed by low-temperature drying.
[0026] As an alternative, a continuous strip removable support layer method can be used. A support layer is formed on the surface of a circulating metal strip using molten paraffin or low-melting-point polyethylene glycol. A sheet-like inorganic matrix is then spread onto the support layer, temporarily shielding one main surface. Fluorinated polyether silane and polyether silane hydrolysate are sprayed onto the exposed main surface and condensed. After removing the support layer, the modified side is re-embedded in a new support layer, and the other main surface is sprayed with aminosilane and / or hydroxysilane hydrolysate.
[0027] This alternative method enables scaled-up production using continuous unwinding, powder spreading, spraying, heating, removal of the support layer, and collection equipment.
[0028] The method for preparing the capillary channel blocking sol includes: 3-Glycidyl etheroxypropyltrimethoxysilane was added to a mixture of water and alcohol, the pH was adjusted to 3.5–5.5, and hydrolyzed at 20–40°C for 30–120 min; nano-silica was added and stirring was continued for 30–90 min, and aged at 20–30°C for 2–24 h to obtain a capillary channel blocking sol.
[0029] The alcohol is selected from one or more of ethanol, isopropanol, and n-propanol.
[0030] The solid content of the aqueous hydroxy acrylic acid dispersion is preferably 38-48 wt%, and the hydroxyl content based on solids is 2.0-4.5 wt%.
[0031] The solid content of the aqueous siloxane-modified polyurethane dispersion is preferably 35-45 wt%, wherein the content of siloxane segments is 5-15 wt%.
[0032] The water-dispersible aliphatic polyisocyanate is selected from hexamethylene diisocyanate trimer, isophorone diisocyanate trimer, or a mixture of the two.
[0033] When component A and component B are mixed, the molar ratio of isocyanate groups to hydroxyl groups is 0.85 to 1.20:1.
[0034] The titanium dioxide is preferably rutile titanium dioxide.
[0035] The inorganic filler is selected from one or more of barium sulfate, wollastonite powder, calcined kaolin, and mica powder.
[0036] The dispersant is preferably a polycarboxylate dispersant or a nonionic polymer dispersant containing pigment affinity groups.
[0037] The defoamer is preferably one or more of mineral oil-based defoamers, organosilicon-based defoamers, and polyether-modified siloxane defoamers.
[0038] The rheology modifier is preferably one or more of the following: associative polyurethane thickener, hydrophobically modified alkali-swellable thickener, and hydroxyethyl cellulose.
[0039] The coating is suitable for concrete or inorganic mortar surfaces. It is preferable to apply a water-based epoxy penetrating sealant or a water-based acrylic penetrating sealant to the substrate before application.
[0040] The active hydrogen groups include hydroxyl groups in aqueous hydroxyl acrylic dispersions and aqueous siloxane-modified polyurethane dispersions, as well as amino and hydroxyl groups on the second main surface of double-sided Janus sheet-like anti-smoke particles.
[0041] The fluorinated polyether silane is a silane compound that simultaneously contains fluorinated polyether segments and at least one hydrolyzable trialkoxysilane group; the polyether silane is a silane compound that simultaneously contains polyoxyethylene segments and at least one hydrolyzable trialkoxysilane group.
[0042] The finishing coating forms one or two layers of finishing film with a total dry film thickness of 80–180 μm.
[0043] A method for preparing a stain-resistant tunnel wall coating includes the following steps: S1. Mix water, dispersant and part of defoamer, add titanium dioxide and inorganic filler, and disperse at 2000-4000 r / min for 20-40 min to obtain pigment and filler slurry; S2. Reduce the rotation speed to 500-1000 r / min, add waterborne hydroxy acrylic dispersion and waterborne siloxane modified polyurethane dispersion to the pigment and filler slurry in sequence, stir for 15-30 min to obtain the base material; S3. Control the base material temperature to 20-35℃, add double-sided Janus flake anti-smoke particles at a stirring linear speed of 0.5-2.0m / s, stir for 10-30 minutes, add capillary channel blocking sol, then add rheology modifier, remaining defoamer and water, adjust the viscosity, defoam and filter to obtain component A. S4. The water-dispersible aliphatic polyisocyanate is packaged separately as component B. Before use, component A and component B are mixed to obtain a stain-resistant tunnel wall coating.
[0044] Before adding the base material, double-sided Janus flake anti-smoke granules are preferably mixed with waterborne siloxane-modified polyurethane dispersion, water and nonionic wetting agent at a mass ratio of 1:0.5-2.0:0.5-2.0:0.01-0.08 to prepare a granular pre-dispersion slurry with a solid content of 20-45 wt%.
[0045] The pre-dispersed slurry is added to the base material within 5–20 minutes. After the pre-dispersed slurry is added, dispersion operations with a stirring linear velocity higher than 2.0 m / s are no longer used to avoid breakage, tumbling, and agglomeration of the flaky particles.
[0046] The capillary channel blocking sol was added within 5 to 20 minutes after the addition of the double-sided Janus sheet-like anti-smoke granules, at a system temperature of 20 to 30°C and a pH of 7.5 to 8.5.
[0047] The solid content of the obtained component A is 45–60 wt%.
[0048] Add component B before construction and stir at 400-800 rpm for 3-8 minutes.
[0049] Application methods include spraying or roller coating, with a single wet film thickness of 60–150 μm. The interval between two consecutive applications is 2–12 hours, and the coating is cured at 10–35°C.
[0050] Compared with the prior art, the present invention provides a stain-resistant tunnel wall coating and its preparation method, which has the following beneficial effects: it does not rely solely on increasing the water contact angle, but rather suppresses diesel oil fume pollution through three functions: air-side oil repellency and pollution release, substrate-side chemical anchoring, and layer edge channel sealing.
[0051] The first main surface of the double-sided Janus sheet-like anti-smoke particles simultaneously contains fluorinated polyether segments and polyoxyethylene segments. The fluorinated polyether segments can reduce the adhesion of oily contaminants, while the polyoxyethylene segments form a hydration layer during water washing, thus achieving both low contaminant adhesion under dry conditions and contaminant release under water washing conditions.
[0052] The amino and / or hydroxyl groups on the second primary surface can form chemical bonds with the isocyanate cross-linking network, reducing the problem of ordinary symmetrical hydrophobic particles falling off during long-term washing due to insufficient interfacial bonding.
[0053] Capillary channel blocking sol containing 3-glycidyl etheroxypropyltrimethoxysilane hydrolysate and nano-silica can form a silicon-oxygen network at the edge of the sheet and the interface of the filler, reducing the path of oil fume organic phase into the interior of the coating surface. Attached Figure Description
[0054] Figure 1 The ² of the cross-section of the double-sided Janus glass flake particles used in Embodiment 2 of the present invention 8 Si - Ion surface distribution diagram; Figure 2 The cross-section of the double-sided Janus glass flake particles used in Embodiment 2 of the present invention is ¹ 9 F - Ion surface distribution diagram; Figure 3 The ¹²C¹ of the cross-section of the double-sided Janus glass flake particles used in Embodiment 2 of the present invention 4 N - Ion surface distribution diagram; Figure 4 This is a focused ion beam scanning electron microscope image of the cross section of the stain-resistant tunnel wall coating obtained in Embodiment 2 of the present invention; Figure 5 This is a FIB-SEM cross-sectional view of the double-sided Janus glass flakes staggered arrangement and the tightly sealed edge structure of the flakes in the coating obtained in Example 2 of the present invention; Figure 6 This is a FIB-SEM cross-sectional view of the coating obtained in Example 2 of the present invention after 2000 washes, showing the state of the interface between the double-sided Janus glass flakes and the resin matrix. Figure 7 This is a graph showing the interfacial adhesion force curves of the coating obtained in Example 2 of the present invention to diesel droplets in both the dry and hydrated states. Detailed Implementation
[0055] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0056] Please see Figures 1-7 This invention provides a technical solution for a stain-resistant tunnel wall coating and its preparation method: Unless otherwise stated, all "parts" refer to parts by weight, and all percentages refer to percentages by weight.
[0057] Each performance test uses three parallel test plates. For repeatable quantitative indicators such as color difference, cleaning recovery rate, residual oily substances, stain resistance, water contact angle, number of washes, and drying time, the test results are expressed as mean ± standard deviation. For grade or qualitative indicators such as adhesion level and water resistance appearance, the result is reported when the results of the three test plates are consistent, and the worst grade or most unfavorable phenomenon is reported when the results are inconsistent.
[0058] Raw material description The aqueous hydroxy acrylic acid dispersion HAA-1 has a solid content of 40 wt%, a hydroxyl content of 2.0 wt% on a solid basis, and a pH of 8.0.
[0059] The aqueous hydroxy acrylic acid dispersion HAA-2 has a solid content of 45 wt%, a hydroxyl content of 3.2 wt% on a solid basis, and a pH of 8.2.
[0060] The aqueous hydroxy acrylic acid dispersion HAA-3 has a solid content of 42 wt%, a hydroxyl content of 4.5 wt% on a solid basis, and a pH of 8.3.
[0061] The waterborne siloxane-modified polyurethane dispersion SPU-1 has a solid content of 38 wt% and a siloxane segment content of 5 wt%.
[0062] The solid content of the waterborne siloxane-modified polyurethane dispersion SPU-2 is 40 wt%, and the siloxane segment content is 10 wt%.
[0063] The solid content of the waterborne siloxane-modified polyurethane dispersion SPU-3 is 42 wt%, and the siloxane segment content is 15 wt%.
[0064] The water-dispersible aliphatic polyisocyanate is a hydrophilic modified hexamethylene diisocyanate trimer with an NCO content of 23.5 wt%. In Example 6, a mixture of hexamethylene diisocyanate trimer and isophorone diisocyanate trimer in a mass ratio of 3:1 was used.
[0065] The average particle sizes of the nano-silica are 8 nm, 18 nm and 30 nm.
[0066] The titanium dioxide is rutile titanium dioxide.
[0067] The nonionic wetting agent is a polyether-modified siloxane wetting agent.
[0068] Preparation Example 1 Preparation of double-sided Janus-synthetic fluorinated phlogopite particles JP-1 The median particle size of the synthetic fluorophlogopite used was 6 μm, the average thickness was 0.20 μm, and the aspect ratio was 30.
[0069] 100 parts of synthetic fluorophlogopite were pre-wetted with deionized water to control the moisture content of the particles to 25 wt%.
[0070] 300 parts of low-aromatic isoalkanes were added as the oil phase to a reaction vessel equipped with an interface feeder, along with 6 parts of fluorinated polyether silane and 2 parts of polyether silane. The fluorinated polyether silane had a number-average molecular weight of 500 for the fluorinated polyether segments and a ethylene oxide unit content of 60 mol%.
[0071] Add 400 parts of deionized water to the reaction vessel as the aqueous phase, and add 5 parts of 3-aminopropyltriethoxysilane. Adjust the pH of the aqueous phase to 4.8 with acetic acid and allow the silane to pre-hydrolyze for 30 minutes.
[0072] Pre-wetted synthetic fluorophlogopite was added to the oil-water interface through a slit feeder and reacted at 45°C under low shear for 0.5 h.
[0073] After the reaction was completed, the particles were subjected to sedimentation and phase separation, filtered, washed successively with isopropanol and deionized water, and dried under vacuum at 60°C for 6 hours to obtain double-sided Janus synthetic fluorophlogopite particles JP-1.
[0074] Preparation Example 2 Preparation of double-sided Janus glass flake particles JP-2 The median particle size of the glass flakes used was 15 μm, the average thickness was 0.25 μm, and the aspect ratio was 60.
[0075] Referring to Preparation Example 1, the mass ratio of fluorinated polyether silane to polyether silane was adjusted to 6:1, the number-average molecular weight of the fluorinated polyether segments was 1500, and the content of ethylene oxide units in the polyether silane was 80 mol%.
[0076] The aqueous phase is a mixture of 3-aminopropyltriethoxysilane and hydroxysilane in a mass ratio of 2:1.
[0077] The reaction temperature was 60℃, the reaction time was 1.5h, and the other conditions were the same as in Preparation Example 1, to obtain double-sided Janus glass flake particles JP-2.
[0078] Preparation Example 3 Preparation of double-sided Janus sheet-like alumina particles JP-3 The median particle size of the flake alumina used was 25 μm, the average thickness was 0.21 μm, and the aspect ratio was 119.
[0079] The mass ratio of fluorinated polyether silane to polyether silane is 9:1, the number-average molecular weight of fluorinated polyether segments is 3000, and the content of ethylene oxide units in polyether silane is 100 mol%.
[0080] Hydroxysilane is used in the aqueous phase.
[0081] The reaction temperature was 75℃, the reaction time was 3h, and the other conditions were the same as in Preparation Example 1, resulting in double-sided Janus sheet-like alumina particles JP-3.
[0082] Preparation Example 4 Preparation of double-sided Janus plate-shaped boron nitride particles JP-4 The median particle size of the boron nitride flakes used was 24 μm, the average thickness was 0.80 μm, and the aspect ratio was 30.
[0083] The mass ratio of fluorinated polyether silane to polyether silane is 5:1, the number-average molecular weight of fluorinated polyether segments is 1800, and the content of ethylene oxide units in polyether silane is 85 mol%.
[0084] The aqueous phase is a mixture of 3-aminopropyltrimethoxysilane and hydroxysilane in a mass ratio of 1:1.
[0085] The reaction temperature was 62℃, the reaction time was 2h, and the other conditions were the same as in Preparation Example 1, resulting in double-sided Janus plate-shaped boron nitride particles JP-4.
[0086] Preparation Example 5 Continuous preparation of double-sided Janus glass flake particles JP-5 A horizontal oil-water interface reactor with an effective volume of 1 m³ was used.
[0087] The oil and water phase compositions were the same as in Preparation Example 2. The oil phase volume was 350 L and the water phase volume was 450 L. Pre-wetted glass flakes were added to the oil-water interface at a rate of 20 kg / h through a slit-type distributor with a width of 300 mm.
[0088] The shear rate in the interfacial region within the reactor was controlled to be 35–45 s. - ¹, the temperature was 60±2℃, and the average residence time was 1.5h. The reaction products were continuously overflowed into a sedimentation separator. After the oil phase was separated, the particles were collected by a horizontal centrifuge, washed sequentially with isopropanol and water, and dried in a vacuum belt dryer at 65℃.
[0089] After 8 hours of continuous operation, a total of 151.2 kg of JP-5 was obtained, with a yield of 94.5% based on the theoretical total solids of glass flakes and silane.
[0090] Preparation Example 6 Preparation of double-sided Janus glass flake particles JP-6 by continuous strip removable support layer method A molten paraffin layer with a thickness of 0.3 mm is applied to the surface of a 500 mm wide stainless steel circulating belt. Glass flakes are then evenly spread on the paraffin layer, and a slight vibration is applied to embed one main surface of the glass flakes into the paraffin layer.
[0091] A hydrolysate containing fluorinated polyether silane and polyether silane in a mass ratio of 6:1 was sprayed and condensed at 80°C for 1.5 h. The paraffin was dissolved and recovered using isoparaffins at 70°C. After cleaning the particles, a new paraffin layer was embedded into the modified main surface.
[0092] A hydrolysate of 3-aminopropyltriethoxysilane and hydroxysilane in a mass ratio of 2:1 was sprayed onto the other main surface, and condensation was carried out at 75°C for 1 hour. The paraffin was removed, and the surface was washed and dried to obtain double-sided Janus glass flake particles JP-6.
[0093] Characterization of two-sided properties JP-1 to JP-6 were respectively formed into monolayer particles on the surface of removable pressure-sensitive adhesive, and the X-ray photoelectron spectra of the first main surface and the second main surface after flipping were tested respectively.
[0094] The test results are shown in Table 1.
[0095] Table 1. Surface characterization results of double-sided Janus sheet-like anti-smoke particles
[0096] Table 1 shows that the fluorine content on the first main surface of the particles is significantly higher than that on the second main surface; the second main surface of the particles using aminosilane has a higher nitrogen content, indicating that the two surfaces of the particles have different chemical compositions.
[0097] The particles obtained by the continuous oil-water interface method and the continuous strip support layer method have similar double-sided chemical differences to the particles obtained by the laboratory batch method, indicating that the double-sided particles are feasible for large-scale preparation.
[0098] Comparative Preparation Example 1 Preparation of non-Janus randomly grafted glass flakes RJP-1 The fluorinated polyether silane, polyether silane, 3-aminopropyltriethoxysilane and hydroxysilane used in Preparation Example 2 were simultaneously added to an aqueous ethanol solution for hydrolysis. The glass flakes were then completely immersed in the hydrolysate and reacted at 60°C for 1.5 h.
[0099] The total amount of each silane used was the same as in Preparation Example 2, and the filtration, washing and drying conditions were the same as in Preparation Example 2, resulting in non-Janus glass flakes RJP-1 with the same components randomly grafted onto both sides of the surface.
[0100] Comparative Preparation Example 2 Preparation of symmetrical fluorinated glass flakes SFP-1 Referring to Comparative Preparation Example 1, without adding 3-aminopropyltriethoxysilane and hydroxysilane, fluorinated polyether silane and polyether silane were uniformly grafted onto the entire surface of the glass flakes.
[0101] The total amount of fluorinated polyether silane and polyether silane was the same as in Preparation Example 2, resulting in symmetrical fluorinated glass flakes SFP-1.
[0102] Comparative preparation example 3 Preparation of double-sided particles FPJ-1 without polyoxyethylene segments Referring to Preparation Example 2, the polyether silane was omitted, and the total amount of silane was made up with an equal mass of fluorinated polyether silane. The other conditions were the same as in Preparation Example 2, and double-sided particles FPJ-1 with only fluorinated polyether segments on the first main surface were obtained.
[0103] Preparation of capillary channel blocking sol Preparation Example 7 Capillary channel blocking sol CS-1 3-Glycidyl etheroxypropyltrimethoxysilane was added to a mixture of ethanol and water, the pH was adjusted to 3.5 with acetic acid, and hydrolyzed at 20°C for 30 min.
[0104] Add nano-silica with an average particle size of 8nm, continue stirring for 30min, and age at 20℃ for 2h.
[0105] The hydrolysate of 3-glycidyl etheroxypropyltrimethoxysilane and nano-silica were mixed at a mass ratio of 1:1 based on dry matter, and the resulting CS-1 had a solid content of 15 wt%.
[0106] Preparation Example 8 Capillary channel blocking sol CS-2 Isopropanol and water were used as the hydrolysis medium, the pH was adjusted to 4.5, and hydrolysis was carried out at 30°C for 75 min.
[0107] Add nano-silica with an average particle size of 18 nm, continue stirring for 60 min, and age at 25 °C for 12 h.
[0108] The hydrolysate of 3-glycidyl etheroxypropyltrimethoxysilane and nano-silica were mixed at a mass ratio of 1:2.5 on a dry matter basis, and the resulting CS-2 had a solid content of 25 wt%.
[0109] Preparation Example 9 Capillary channel blocking sol CS-3 n-Propanol and water were used as the hydrolysis medium, the pH was adjusted to 5.5, and hydrolysis was carried out at 40℃ for 120 min.
[0110] Add nano-silica with an average particle size of 30 nm, continue stirring for 90 min, and age at 30 °C for 24 h.
[0111] The hydrolysate of 3-glycidyl etheroxypropyltrimethoxysilane and nano-silica were mixed at a mass ratio of 1:4 based on dry matter, and the resulting CS-3 had a solid content of 35 wt%.
[0112] Comparative preparation example 4 Ordinary nano silica sol NSS-1 An aqueous silica sol with a solid content of 25 wt% was prepared using nano-silica with an average particle size of 18 nm, without the addition of 3-glycidyl etheroxypropyltrimethoxysilane, and the pH was adjusted to 8.0 using ammonia.
[0113] Example 1 The raw material composition, by weight, is as follows: 35 parts of waterborne hydroxy acrylic acid dispersion HAA-1; 10 parts of waterborne siloxane-modified polyurethane dispersion SPU-1; 4 parts of JP-1; 2 parts of CS-1; 10 parts of titanium dioxide; 5 parts of barium sulfate; 0.2 parts of dispersant; 0.1 parts of defoamer; 0.1 parts of rheology modifier; 5 parts of deionized water; 3 parts of water-dispersible aliphatic polyisocyanate.
[0114] The molar ratio of isocyanate groups to hydroxyl groups is 0.85:1.
[0115] Deionized water, dispersant and 0.05 parts of defoamer were mixed, titanium dioxide and barium sulfate were added, and the mixture was dispersed at 2000 r / min for 20 min to obtain pigment and filler slurry.
[0116] Reduce the rotation speed to 500 r / min, add HAA-1 and SPU-1 in sequence, stir for 15 min to obtain the base material.
[0117] JP-1, SPU-1, deionized water and nonionic wetting agent were mixed in a mass ratio of 1:0.5:0.5:0.01 to prepare a pre-dispersed slurry. The slurry was then added to the base material at a temperature of 20°C within 5 minutes, and the stirring speed was 0.5 m / s.
[0118] After stirring for 10 minutes, CS-1 was added 5 minutes after the particles were added, and the system pH was 7.5. Rheology modifier, remaining defoamer, and residual water were added, and the mixture was defoamed and filtered to obtain component A.
[0119] Add component B before application and stir at 400 rpm for 3 minutes. Apply in a single spray coat to achieve a wet film thickness of 100 μm. Cur at 10°C to form a dry film thickness of 80 ± 4 μm.
[0120] Example 2 The raw material composition by weight is as follows: HAA-2 45 parts; SPU-2 17.5 parts; JP-2 8 parts; CS-2 5 parts; titanium dioxide 17.5 parts; barium sulfate 8.0 parts; wollastonite powder 4.5 parts; dispersant 0.8 parts; defoamer 0.45 parts; rheology modifier 0.55 parts; deionized water 12.5 parts; water-dispersible aliphatic polyisocyanate 6.5 parts.
[0121] The molar ratio of isocyanate groups to hydroxyl groups is 1.00:1.
[0122] Mix water, dispersant and part of defoamer, add titanium dioxide and inorganic filler, and disperse at 3000 r / min for 30 min.
[0123] Reduce the rotation speed to 750 r / min, add HAA-2 and SPU-2 in sequence, and stir for 22 min.
[0124] JP-2, SPU-2, water and nonionic wetting agent were mixed in a mass ratio of 1:1.2:1.0:0.04 to prepare a pre-dispersed slurry. The slurry was then added to the base material at a temperature of 25°C within 12 minutes, and the stirring speed was 1.2 m / s.
[0125] After stirring for 20 minutes, CS-2 was added 12 minutes after the granules were added, bringing the system pH to 8.0. The remaining additives were added, the mixture was degassed, and filtered to obtain component A.
[0126] Add component B before application and stir at 600 rpm for 5 minutes. Apply the coating using a two-coat method, with each wet film thickness being 75 μm. The two coats should be applied 6 hours apart. Cure at 23°C to form a dry film thickness of 120 ± 5 μm.
[0127] Example 3 The raw material composition by weight is as follows: 55 parts of aqueous hydroxy acrylic acid dispersion; 25 parts of SPU-3; JP-3 12 parts; CS-3 8 parts; titanium dioxide 25 parts; calcined kaolin 12 parts; wollastonite powder 8 parts; dispersant 1.5 parts; defoamer 0.8 parts; rheology modifier 1.0 part; deionized water 20 parts; water-dispersible aliphatic polyisocyanate 10 parts.
[0128] By selecting an aqueous hydroxyl acrylic dispersion with a hydroxyl content of 3.5 wt% on a solids basis, the molar ratio of isocyanate groups to hydroxyl groups is made to be 1.20:1.
[0129] Pigment and filler slurry was prepared by dispersing at 4000 r / min for 40 min. The rotation speed was then reduced to 1000 r / min, and two resin dispersions were added and stirred for 30 min.
[0130] JP-3, SPU-3, water and nonionic wetting agent were mixed in a mass ratio of 1:2.0:2.0:0.08 to prepare a pre-dispersed slurry. The slurry was then added to the base material at 30°C within 20 minutes, and the stirring speed was 2.0 m / s.
[0131] After stirring for 30 minutes, CS-3 was added 20 minutes after the particles were added, and the pH of the system was 8.5.
[0132] Add component B before application and stir at 800 rpm for 8 minutes. Apply the coating in two coats, each with a wet film thickness of 150 μm, with a 12-hour interval between coats. Cure at 35°C to form a total dry film thickness of 180 ± 6 μm.
[0133] Example 4 Referring to Example 2, JP-2 was replaced with 6 parts of JP-4, CS-2 was adjusted to 3 parts; HAA-2 was 40 parts, SPU-1 was 15 parts, titanium dioxide was 15 parts, inorganic filler was 10 parts, and the remaining raw materials and preparation conditions were the same as in Example 2.
[0134] The dry film thickness of the resulting coating was 116±5μm.
[0135] Example 5 Referring to Example 2, 40 parts of HAA-3, 20 parts of SPU-3, 10 parts of JP-3, 6 parts of CS-2, and 9 parts of water-dispersible aliphatic polyisocyanate were used.
[0136] The molar ratio of isocyanate groups to hydroxyl groups is 1.05:1.
[0137] The remaining raw materials and preparation conditions were the same as in Example 2, and the dry film thickness of the resulting coating was 122±5μm.
[0138] Example 6 Referring to Example 2, JP-2 was replaced with JP-5 prepared by a continuous oil-water interface method; the water-dispersible aliphatic polyisocyanate was a mixture of hexamethylene diisocyanate trimer and isophorone diisocyanate trimer in a mass ratio of 3:1.
[0139] The remaining raw materials and preparation conditions were the same as in Example 2, and the dry film thickness of the resulting coating was 121±4μm.
[0140] When JP-6 is used instead of JP-5, the application conditions and cured film properties of the resulting coating are basically the same as in Example 6.
[0141] Comparative Example 1, referring to Example 2, replaced 8 parts of JP-2 by mass with 8 parts of RJP-1, while keeping the other raw materials and conditions unchanged.
[0142] Comparative Example 2: Referring to Example 2, 8 parts of JP-2 were retained, 5 parts of CS-2 were deleted, and 5 parts of deionized water were added to make up the total mass, while the other conditions remained unchanged.
[0143] Comparative Example 3: Refer to Comparative Example 1, but delete 5 parts of CS-2 and make up the total mass with 5 parts of deionized water, while keeping the other conditions unchanged.
[0144] The only difference between Comparative Example 1 and Comparative Example 3 was whether capillary channel blocking sol was added; the only difference between Comparative Example 2 and Comparative Example 3 was whether the particles had a double-sided Janus structure. Examples 2, 1, 2, and 3 together constitute a comparative system of two-factor crossover and single-factor pairing.
[0145] Comparative Example 4, referring to Example 2, replaced 8 parts of JP-2 with 8 parts of SFP-1, with all other conditions remaining unchanged.
[0146] Comparative Example 5, referring to Example 2, replaces 5 parts of CS-2 with 5 parts of NSS-1, with all other conditions remaining unchanged.
[0147] Comparative Example 6, referring to Example 2, JP-2 was adjusted to 2 parts, and 6 parts of unmodified glass flakes were added to keep the total amount of sheet material at 8 parts, while the other conditions remained unchanged.
[0148] Comparative Example 7, referring to Example 2, adjusted CS-2 to 0.5 parts and added 4.5 parts of ordinary nano silica sol NSS-1, so that the total amount of sol added was kept to 5 parts, and the other conditions remained unchanged.
[0149] Comparative Example 8, referring to Example 2, increased the stirring speed after adding JP-2 from 1.2 m / s to 4.0 m / s, and continued stirring at this speed for 20 minutes, while keeping other conditions unchanged.
[0150] Comparative Example 9, referring to Example 2, replaced 8 parts of JP-2 with 8 parts of FPJ-1, while keeping the other conditions unchanged.
[0151] Performance testing 1. Test plate preparation and curing The stain-resistant, water-resistant, and wash-resistant test panels are made of asbestos-free fiber cement flat plates with dimensions of 150mm×70mm×4mm.
[0152] The same water-based epoxy penetrating sealant was applied to the surface of the test panel, and after curing for 24 hours, the finishing coatings of each example and comparative example were applied.
[0153] Except for the dry film thicknesses of 80 μm and 180 μm in Examples 1 and 3, respectively, the dry film thicknesses of the other groups were controlled at 120 ± 5 μm.
[0154] The test panels were cured for 7 days at a temperature of 23±2℃ and a relative humidity of 50±5%.
[0155] The dry film thickness was determined according to the method specified in GB / T 13452.2—2008 "Determination of film thickness of paints and varnishes".
[0156] 2. Diesel fuel fume pollution and cleaning test A sealed oil fume pollution chamber with a volume of 0.50 m³ was used. The oil fume source was a single-cylinder four-stroke direct injection diesel engine, using the same batch of No. 0 automotive diesel fuel, and the test load was 75% of the rated power.
[0157] After the diesel engine has been running stably for 10 minutes, the exhaust gas is introduced into the pollution chamber via diluted air. The particulate matter concentration in the pollution chamber is controlled at 150±10 mg / m³, the temperature at 40±2℃, the relative humidity at 55±5%, and the airflow velocity on the test plate surface at 1.0±0.1 m / s.
[0158] The test plate was placed vertically and exposed for 2 hours, then removed and left to stand at 23±2℃ for 1 hour.
[0159] After contamination, the sample was first sprayed with deionized water at a pressure of 0.10 MPa and a temperature of 23±2℃ for 60 seconds. The effective contact area of the cleaning head was 25 cm². The surface was covered with non-woven fabric of uniform specifications. The sample was subjected to 10 cycles at a normal load of 9.8 N, a reciprocating stroke of 100 mm and a frequency of 30 times / min. The non-woven fabric was replaced for each sample. Finally, the sample was rinsed with deionized water and dried for 24 hours.
[0160] The basic framework for pollutant application, test panel condition adjustment, cleaning operation, and stain resistance evaluation refers to GB / T 9780—2013 "Test Method for Stain Resistance of Architectural Coatings". The pollutant medium is replaced with the aforementioned diesel fume based on the actual pollution characteristics of tunnel diesel fume.
[0161] 3. Overall color difference and cleaning recovery rate An integrating sphere spectrophotometer was used to measure L before, after, and after cleaning of the sample under D65 light source and 10° standard observer conditions. a and b value.
[0162] Color difference was measured and calculated according to the method specified in the national standard GB / T 11186—2025 "Method for measuring the color of coating".
[0163] The overall color difference is calculated using the following formula: ΔE ab = [(ΔL] )²+(Δa )²+(Δb )²]¹ ².
[0164] The cleaning recovery rate is calculated using the following formula: Cleaning recovery rate / % = (ΔE after contamination - ΔE after cleaning) / ΔE after contamination × 100%.
[0165] 4. Repeated contamination – cleaning cycle Five consecutive pollution-cleaning cycles were conducted according to the diesel fume pollution and cleaning test method.
[0166] After each cycle, dry for 24 hours at 23±2℃ and 50±5% relative humidity before starting the next cycle.
[0167] The overall color difference after the 5th cleaning and drying is taken as the residual color difference after 5 cycles.
[0168] 5. Quality of residual oily substances After completing a diesel fume pollution and cleaning process, a 100cm² test plate surface was quantitatively rinsed with 20mL of n-hexane.
[0169] The rinsing solution was filtered through a 0.45 μm polytetrafluoroethylene filter membrane, n-hexane was removed by vacuum distillation at 60 °C, and the solution was cooled to constant weight in a desiccator.
[0170] The mass of residual oily substances is converted to mg / m² based on the area of the test plate.
[0171] Each group of tests consists of 3 test plates, and uncontaminated blank test plates are set up for quality calibration.
[0172] 6. Standard stain resistance The stain resistance of architectural coatings shall be tested according to the test method specified in GB / T 9780—2013, and the stain resistance rate shall be reported. The lower the stain resistance rate, the less the reflectivity of the coating decreases after the pollution treatment.
[0173] 7. Static water contact angle Referring to the optical measurement principle of GB / T 30693—2014 "Measurement of the contact angle between plastic film and water", 5 μL of deionized water was added to the surface of the cured coating, and the contact angle was measured after standing for 10 seconds. Five positions were measured for each test plate.
[0174] Since the standard object of GB / T 30693—2014 is plastic film, this implementation method only refers to its optical contact angle measurement principle, and ensures the comparability of the results of each group by standardizing droplet volume, standing time, ambient temperature and number of sampling points.
[0175] The water contact angle data is only used to illustrate that there is not a simple correspondence between the water contact angle and the anti-fouling performance of diesel oil fumes, and is not used as a necessary structural parameter to define the technical solution of the present invention.
[0176] 8. Adhesion The cross-cut test was conducted according to GB / T 9286—2021 "Paints and Varnishes - Cross-cut Test", with a cross-cut spacing of 2 mm.
[0177] 9. Washability The test was conducted according to GB / T 9266—2009 "Determination of Washability of Architectural Coatings", and the number of washes before the substrate was exposed was recorded.
[0178] 10. Water resistance The water immersion test was conducted according to GB / T 1733—1993 "Test Method for Water Resistance of Coating Films" for 168 hours. The coating film was observed to see if blistering, cracking, peeling, obvious discoloration or loss of gloss occurred.
[0179] 11. Drying time The surface drying time was determined according to GB / T 1728—2020 "Determination of Drying Time of Paint Film and Putty Film".
[0180] Performance test results Table 2 Diesel Fume Pollution and Cleaning Performance
[0181] Table 3. Conventional physical properties of the coating film
[0182] Note: The quantitative indicators in Tables 2 and 3 are the average ± standard deviation of three parallel test panels. The cross-cut adhesion grade and water resistance appearance are typical results when the results of the three test panels are consistent; when the results are inconsistent, the worst grade or the most unfavorable appearance phenomenon is reported as the result.
[0183] Figure 1 In the figure, mark 1 represents the inorganic matrix region of glass flakes, mark 2 and mark 4 represent the first main surface and the second main surface, mark 6 represents the embedded resin region, mark 7 represents the ion signal intensity scale, X represents the extension direction of the main surface of the flake particles, Z represents the thickness direction, and the scale L is 2μm.
[0184] Figure 2 In the figure, label 1 represents the inorganic matrix region of the glass flakes, label 2 represents the first main surface, and label 3 represents the region near the first main surface. 9 F - The enriched region is marked with 4 to indicate the second primary surface, 6 to indicate the resin-embedded region, and 7 to indicate the ion signal intensity scale, with scale L being 2 μm.
[0185] Figure 3In the figure, label 1 represents the inorganic matrix region of the glass flakes, labels 2 and 4 represent the first and second main surfaces, respectively, and label 5 represents the ¹²C¹ region near the second main surface. 4 N - The enriched region is marked with 6 to indicate the resin-embedded region and 7 to indicate the ion signal intensity scale, with scale L being 2 μm.
[0186] Figure 4 In the diagram, the blue area represents² 8 Si - Glass substrate, green area indicates the vicinity of the first primary surface¹ 9 F - The enriched layer, with the yellow area representing the vicinity of the second primary surface¹²C¹ 4 N - The enriched layer indicates that the two types of functional groups are distributed on opposite sides of the particle, with a scale bar L of 2 μm.
[0187] Figure 5 In the figure, 1 represents the air-side surface of the coating, 2 represents the cross-linked resin matrix, 3 represents double-sided Janus glass flake particles, 4 represents the overlapping area of the flakes, 5 represents the densely filled area at the edge and interface of the flakes, 6 represents titanium dioxide and inorganic fillers, 7 represents the platinum protective layer, A and B represent the thickness direction and the flake extension direction, respectively, and the scale bar L is 10 μm.
[0188] Figure 6 In the figure, mark 1 represents the air-side surface of the coating after washing, mark 2 represents the cross-linked resin matrix, mark 3 represents the double-sided Janus glass flake particles, mark 4 represents the continuous contact interface between the particles and the resin matrix, mark 5 represents the densely filled area at the edge of the flakes, mark 6 represents titanium dioxide and inorganic fillers, mark 7 represents the platinum protective layer, and the scale bar L is 10 μm.
[0189] Figure 7 In the diagram, curves a and b represent the dry state and the pre-hydrated state, respectively. P1 to P4 represent the starting point of the pullback, the end point of the loading, the position of the maximum negative adhesion force, and the position of the droplet's complete detachment, respectively. F_ad,dry and F_ad,hyd represent the maximum interfacial adhesion force in the two states, respectively. The shaded area S represents the apparent pull-off work.
[0190] Test Result Analysis Examples 1, 2, and 3 respectively cover the lower, middle, and upper limits of the main components and preparation parameters of the coating. The overall color difference after cleaning in all three examples is no higher than 6.8, and the residual color difference after five contamination-cleaning cycles is no higher than 8.9, indicating that the present invention can achieve the anti-fouling effect of diesel oil fumes within the defined numerical range, rather than being effective only at a single isolated formulation point.
[0191] Example 2 exhibits superior overall performance, with a post-cleaning color difference of 5.3±0.3, a cleaning recovery rate of 86.5±1.0%, a residual color difference of 7.1±0.4 after 5 cycles, and a residual oily substance concentration of 18±2 mg / m².
[0192] Example 4 demonstrates that plate-like boron nitride can replace glass flakes to form a structure resistant to oil fume contamination. Example 5 shows that increasing the hydroxyl content of the hydroxyl acrylic acid dispersion and using plate-like alumina still achieves good stain resistance and adhesion properties. Example 6 uses continuously prepared double-sided Janus particles, whose properties are similar to those of Example 2, indicating that the laboratory preparation method can be scaled up to continuous industrial production.
[0193] Comparative Example 1 used non-Janus randomly grafted particles. Although the type and total amount of silane were the same as in Example 2, the overall color difference after washing increased from 5.3±0.3 to 13.8±0.6, and the residual color difference after 5 cycles increased from 7.1±0.4 to 18.9±0.8. This indicates that the technical effect is not simply due to the mixed addition of fluorinated polyether silane, polyether silane, and aminosilane, but is related to the asymmetric structure of different segments located on different main surfaces of the particles.
[0194] Comparative Example 2 retained double-sided Janus particles but did not add capillary channel blocking sol. Its overall color difference after cleaning was 12.9±0.6, the residual color difference after 5 cycles was 17.4±0.7, and the residual oily substance was 57±4 mg / m². This indicates that relying solely on the oil-repellent and hydration-based release effects of the exposed surface is insufficient to fully prevent oily contaminants from penetrating along the edges of the sheets and the resin-filler interface.
[0195] Comparative Example 3, which lacks both Janus structure and capillary channel blocking sol, exhibited a residual color difference of 26.8±1.0 after 5 cycles and a residual oily substance of 94±6 mg / m². This indicates that the relationship between the double-sided Janus particles and the capillary channel blocking sol is not a simple additive one, but rather a synergistic effect of superaddition.
[0196] The reason lies in the fact that the double-sided Janus sheet particles form a low-pollution adhesion surface on the air side and a reactive anchoring interface on the substrate side, while the capillary channel-sealed sol can condense at the edges of the already anchored sheet particles. Particle anchoring improves the stability of the closed network during cleaning and scrubbing, and the closed network reduces the entry of oil fumes from the edges of the sheets into the space beneath the particles, allowing the oil-repellent and contaminant-releasing effect of the first primary surface to continue to function.
[0197] The actual effect produced by this synergistic effect is significantly greater than the simple sum of the individual effects of the two techniques. It cannot be directly derived from the known effects of either the double-sided Janus sheet particles or the capillary channel blocking sol. This is an unexpected technical effect for those skilled in the art.
[0198] Comparative Example 4 uses symmetrical fluorinated particles with high fluorine content on both sides. Its initial water contact angle reaches 121±3°, which is higher than that of Example 2. However, the overall color difference and residual oily substances after cleaning are significantly higher than those of Example 2. The cross-cut adhesion and scrub resistance are also significantly reduced.
[0199] The results demonstrate that increasing the water contact angle alone is insufficient to solve the problem of irreversible blackening of diesel fumes. Because the symmetrical fluorinated particles lack an anchoring surface for reaction with the isocyanate matrix, the water contact angle decreased from 121±3° to 93±3° after washing, indicating that the durability of its low surface energy structure is significantly lower than that of the double-sided anchoring structure of this invention.
[0200] Comparative Example 5 used ordinary nano-silica sol without epoxy silane hydrolysates. Although ordinary silica sol could fill some gaps, its overall color difference after cleaning was still 11.6±0.5, which was significantly higher than 5.3±0.3 in Example 2. This indicates that the simple physical filling of nano-silica cannot replace the capillary channel sealing sol with silane condensation and interfacial reaction capabilities.
[0201] Comparative Examples 6 and 7 reduced the effective amount of double-sided Janus particles and the effective amount of reactive blocking sol to below the range, respectively. The resulting coating properties were between those of the complete technical solution and the system lacking the corresponding components, indicating that using 4 parts of double-sided Janus particles and 2 parts of capillary channel blocking sol as the lower limit of the range has corresponding experimental basis.
[0202] Comparative Example 8, with the addition of double-sided Janus flake particles under high shear conditions, showed a decrease in the number of wash cycles to 8000±410, and an increase in residual color difference to 17.0±0.8 after 5 cycles. High shear easily causes the flake particles to break, tumble, and agglomerate, weakening their effective spreading and interfacial anchoring on the coating surface. Therefore, it is necessary to control the stirring linear velocity after adding the particles to below 2.0 m / s.
[0203] The first main surface of Comparative Example 9 contained only fluorinated polyether segments, and its initial water contact angle reached 119±3°, but the clean recovery rate was only 75.1±1.3%, lower than 86.5±1.0% of Example 2. This indicates that the polyoxyethylene segments form a hydration interface and promote the removal of pollutants during water washing, which plays an important role in reducing diesel fuel residue.
Claims
1. A stain-resistant tunnel wall coating, characterized in that, The product comprises component A and component B. By weight, component A comprises 35-55 parts of aqueous hydroxyl acrylic dispersion, 10-25 parts of aqueous siloxane-modified polyurethane dispersion, 4-12 parts of double-sided Janus sheet-like anti-smoke particles, 2-8 parts of capillary channel blocking sol, 10-25 parts of titanium dioxide, 5-20 parts of inorganic filler, 0.2-1.5 parts of dispersant, 0.1-0.8 parts of defoamer, 0.1-1.0 parts of rheology modifier, and 5-20 parts of water. Component B comprises 3-10 parts of water-dispersible aliphatic polyisocyanate. The double-sided Janus sheet-like anti-smoke particles comprise a sheet-like inorganic matrix, wherein the first main component of the sheet-like inorganic matrix... The surface is grafted with fluorinated polyether segments and polyoxyethylene segments, and the second main surface is grafted with amino and / or hydroxyl groups; the capillary channel blocking sol is composed of 3-glycidyl etheroxypropyltrimethoxysilane hydrolysate and nano-silica with a particle size of 8-30 nm at a dry matter mass ratio of 1:1-4, and its solid content is 15-35 wt%; during the curing process, the amino and / or hydroxyl groups on the second main surface react with the water-dispersible aliphatic polyisocyanate, and the silanol groups in the capillary channel blocking sol condense at the edges of the double-sided Janus sheet-like anti-smoke particles and at the interface between the double-sided Janus sheet-like anti-smoke particles and the resin matrix to form a silicon-oxygen network; The inorganic filler is selected from one or more of barium sulfate, wollastonite powder, calcined kaolin, and mica powder.
2. The stain-resistant tunnel wall coating according to claim 1, characterized in that, The sheet-like inorganic matrix is selected from one or more of synthetic fluorophlogopite, glass flakes, sheet-like alumina, and sheet-like boron nitride; the median particle size of the sheet-like inorganic matrix is 6-25 μm, the thickness is 0.15-0.80 μm, and the aspect ratio is 30-120.
3. The stain-resistant tunnel wall coating according to claim 1 or 2, characterized in that, The first main surface is formed by grafting fluorinated polyether silane and polyether silane together, wherein the mass ratio of fluorinated polyether silane to polyether silane is 3 to 9:1; the number average molecular weight of the fluorinated polyether segments is 500 to 3000, and the molar content of ethylene oxide units in the polyoxyethylene segments is 60 to 100%; the second main surface is formed by grafting aminosilane and / or hydroxysilane.
4. The stain-resistant tunnel wall coating according to claim 3, characterized in that, The double-sided Janus flake-shaped anti-fouling particles are prepared by an oil-water interface selective grafting method, specifically including: J1. The sheet-like inorganic matrix is pre-wetted with water, and the pre-wetted sheet-like inorganic matrix is continuously added between the immiscible oil phase and the water phase, so that the sheet-like inorganic matrix spreads at the oil-water interface. J2. The oil phase contains fluorinated polyether silane and polyether silane, and the aqueous phase contains hydrolysates of amino silane and / or hydroxy silane. The reaction is carried out at 45-75°C for 0.5-3 hours, so that the first main surface facing the oil phase is grafted with fluorinated polyether segments and polyoxyethylene segments, and the second main surface facing the aqueous phase is grafted with amino and / or hydroxyl groups. J3. The reaction product is continuously filtered and washed, and dried at 40-80°C to obtain the double-sided Janus sheet-like anti-smoke particles.
5. The stain-resistant tunnel wall coating according to claim 1, characterized in that, The capillary channel blocking sol is prepared by the following method: 3-glycidyl etheroxypropyltrimethoxysilane is added to a mixture of water and alcohol, the pH is adjusted to 3.5-5.5, and hydrolyzed at 20-40°C for 30-120 min; the nano-silica is added and stirring is continued for 30-90 min, and aged at 20-30°C for 2-24 h to obtain the capillary channel blocking sol; the alcohol is selected from one or more of ethanol, isopropanol and n-propanol.
6. The stain-resistant tunnel wall coating according to claim 1, characterized in that, The aqueous hydroxyl acrylic dispersion has a hydroxyl content of 2.0–4.5 wt% on a solid basis; the aqueous siloxane-modified polyurethane dispersion has a siloxane segment content of 5–15 wt%; the aqueous aliphatic polyisocyanate is one or both of hexamethylene diisocyanate trimer and isophorone diisocyanate trimer; after mixing component A and component B, the equivalent ratio of isocyanate groups to active hydrogen groups in the system that can react with isocyanate groups is 0.85–1.20:
1.
7. A method for preparing a stain-resistant tunnel wall coating according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Mix water, dispersant and part of defoamer, add titanium dioxide and inorganic filler, and disperse at 2000-4000 r / min for 20-40 min to obtain pigment and filler slurry; S2. Reduce the rotation speed to 500-1000 r / min, add waterborne hydroxy acrylic dispersion and waterborne siloxane modified polyurethane dispersion to the pigment and filler slurry in sequence, stir for 15-30 min to obtain the base material; S3. Control the temperature of the base material to 20-35℃, add double-sided Janus flake anti-smoke particles under the condition of stirring linear speed of 0.5-2.0m / s, stir for 10-30min, add capillary channel blocking sol, then add rheology modifier, remaining defoamer and water, adjust viscosity, defoam and filter to obtain component A. S4. The water-dispersible aliphatic polyisocyanate is packaged separately as component B. Before use, component A and component B are mixed to obtain the stain-resistant tunnel wall coating.
Citation Information
Patent Citations
Extreme-environment-resistant water-based composite coating for new energy automobile interiors and preparation method, use method and application of extreme-environment-resistant water-based composite coating
CN122213776A
Fluorine-containing multifunctional microspheres and uses thereof
US20120296029A1